Defining Social Innovation - Stanford Graduate School of Business (Stanford Graduate School of Business, 2021)
Social innovation is the process of developing and deploying effective solutions to challenging and often systemic social and environmental issues in support of social progress. Social innovation is not the prerogative or privilege of any organizational form or legal structure. Solutions often require the active collaboration of constituents across government, business, and the nonprofit world.
Keywords: Centre de recherche universitaire; Libre accès; États-Unis